1986
DOI: 10.1259/0007-1285-59-706-975
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-section radionuclide tomography of the kidney: a clinical evaluation

Abstract: The clinical utility of radionuclide emission tomography of the kidney in comparison with conventional gamma-camera imaging has been assessed from scans of 60 patients suspected of having space-occupying lesions of the kidney. Nineteen patients had renal tumour, 17 had cysts and seven had renal pseudotumours; the remainder had no lesion. Objective trials using four observers showed only a slight, statistically insignificant advantage from the addition of tomographic sections to conventional images. However, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The relationship between 99m Tc-DMSA imaging findings and clinical outcome (e.g. histology and clinical follow-up) was not directly reported by Williams et al, 5 although it is implied that solid renal tumours do not normally show 99m Tc-DMSA uptake.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The relationship between 99m Tc-DMSA imaging findings and clinical outcome (e.g. histology and clinical follow-up) was not directly reported by Williams et al, 5 although it is implied that solid renal tumours do not normally show 99m Tc-DMSA uptake.…”
Section: Discussionmentioning
confidence: 89%
“…4 Williams et al 5 reported the use of 99m Tc-DMSA scintigraphy in 60 patients with suspected renal masses (mainly on intravenous urography) in 1986, and specifically looked at whether SPECT offered additional information over planar imaging. This included 19 patients with a renal tumour, 17 patients with renal cysts, 7 patients with pseudotumours (column of Bertin, cortical nodule) and 17 patients in whom no renal lesion was found on either 99m Tc-DMSA or ultrasound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17 ] The false positive results have been reported as 10% in the literature on renal space occupying lesions. [ 18 ] Tc-99m DMSA uptake in a thin cortex due to hydronephrosis was so prone to being affected by the partial volume effects in SPECT that it appeared as decreased uptake areas mimicking renal scars. In this context, regional uptake defects which are demonstrated by DMSA scintigraphy may include not only renal scars but also some false positives and other abnormalities as cited above, particularly in heterogeneity of the studied population.…”
Section: Discussionmentioning
confidence: 99%
“…Single photon emission computed tomography (SPECT) provides 3D reconstructions of the imaged kidney, leading to definite localization of the suspected mass and especially useful when multiple small FPT’s are present in a complex scarred kidney architecture. SPECT images can be fused with images obtained from the patient’s corresponding CT or MRI study and hence add specificity [ 16 , 17 ]. Compared to planar DMSA, SPECT DMSA increases the sensitivity in regard to picking up more abnormalities that might be less detectable on 2D planar images that represent multiple planes superimposed on each other and displayed as a 2D image.…”
Section: Introductionmentioning
confidence: 99%